PENGARUH PENERAPAN GREEN ACCOUNTING DAN BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN TAMBANG YANG TERDAFTAR DI BEI PERIODE 2020-2024 - Wahyu Septia Azmi; Budi Rismayadi; Hendri Nur Ardiansyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This study aims to analyze the implementation of green accounting in environmental management and its impact on the financial performance of mining companies listed on the IDX during the 2020-2024 period and that allocate funds for community development programs (CSR) in the 2020-2024 period. This research is quantitative, using secondary data in the form of annual reports from 12 companies that published annual reports consecutively during 2020-2024. The research sample was selected using a purposive sampling method. Data analysis was conducted using SPSS version 22 and multiple linear regression techniques. The results of the study indicate that the implementation of green accounting affects financial performance, environmental costs do not affect financial performance, and both green accounting and environmental costs affect financial performance. The implication of this research is that it can encourage companies to integrate the implementation of green accounting and environmental costs into their business strategies. Companies should no longer view environmental cost reporting merely as a reporting obligation, but should make it a strategic tool for decision-making. At the same time, green accounting should serve as evidence of commitment in practice. This synergistic combination can help companies achieve financial performance profitability.